A ressignificação da questão ambiental em contexto de ruralidade: para uma leitura crítica do Paradoxo de Giddens - Madureira, Gabriel Alarcon (2013)
Reports from IPCC (Intergovernmental Panel on Climate Change) call attention to the possibility of water shortages, to the collapse of the Amazon system, to the biodiversity crisis, and to the proliferation of extreme weather events. Anthony Giddens, British sociologist formulator of the theory of structuration, elaborates an analytical category appointing precisely the lack of concrete actions related to this environmental issue in the policy and in the daily practices. According to him, when practical measures for protecting the environment are put into practice, there will not be enough time to reverse the environmental collapse, setting the self-styled Giddens‟s Paradox. Such point of view of environmental question transforms in normative, abstract and universal, leaving to conceive it as eminently contextual - result of the interaction between individuals, groups and institutions. Precisely so it this research takes this analytical category as a starting point for a relational approach of environmental issues through his own theory of structuration. So, the environment and the nature are now considered as structural principles: as rules and resources mobilized in the reproduction and transformation of social life and, therefore, as objects of appointment disputes and discursive resignifications. In order to analyze sociologically the relational aspect the environmental issue through a qualitative research - theoretically and methodologically linked to the theory of structuration the county of Brotas (São Paulo/Brazil) was established as case study. Are used as research methods: semi-structured interviews, snowball technique, documental survey, photo documentation and socioeconomic questionnaire. This particular location shows a convergence between the multiple conceptions of the environmental issue, the professionalization of ecotourism and of the discursive resignification of the rural areas, allowing the visualization of multiple cognitive perceptions of the environmental issue. The critical debate from Giddens enabled the analysis of four social processes of resignification in the Brotas county: a) The Jacaré-Pepira River; b) From the "hole" to the tourist attraction; c) From Radical to Disneyland; and d) The Estrada do Patrimônio . In summary, the trajectory of the dissertation seeks to discuss sociologically that the environmental issue does not arise in everyday life in a universal and normative form, but eminently as cognitive perception linked to the complexity of knowingness agents.